Investigation into the Oil Recovery Process Using an Organic Alkali-Amino Acid-Based Surfactant System - Tackie-Otoo, B.N. (American Chemical Society, 2021)
The development of combinatory flooding has evolved over the years to utilize the synergies that come into play upon combining more than one chemical agent in a chemical flooding process. This study focuses on investigating the synergies that exist in combining monoethanolamine (ETA) and sodium cocoyl alaninate (SCA) as an alkali-surfactant (AS) formulation for the enhanced oil recovery process. A conventional formulation made of sodium carbonate (Na2CO3) and sodium dodecyl sulfate (SDS) was used for a comparative purpose. The proposed formulation proved to be compatible with the prepared hard brine. The ETA-SCA combination proved superior to Na2CO3-SDS in interfacial tension (IFT) reduction and wettability alteration. Addition of ETA to SCA synergistically reduced IFT to a low value of 4.73 Ã 10-2 mN/m at a surfactant concentration lower than the critical micelle concentration (CMC). ETA also played a synergistic role in improving the wetting power of SCA on quartz surface. The formulation also showed a high emulsifying ability owing to its superior IFT reduction capability. Static adsorption studies showed SCA to exhibit Langmuir-type adsorption behavior similar to SDS. The adsorption of SCA onto a sand surface was favorable, but ETA proved to reduce adsorption of SCA effectively at 0.3 wt . The ETA-SCA and Na2CO3-SDS systems achieved additional oil recoveries of 31 and 25 original oil in place (OOIP) over conventional core flooding, respectively. The proposed AS formulation, therefore, showed better recovery potential in addition to its environmentally friendly nature. Â© 2021 American Chemical Society.